2022
DOI: 10.3389/fimmu.2022.888918
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Change of the Lung and Bowel in an Ulcerative Colitis Rat Model and the Protective Effect of Sodium Houttuyfonate Combined With Matrine

Abstract: ObjectiveTo explore the immune change of lung injury of Ulcerative colitis (UC) by observing the changes of inherent immunity and adaptive immunity of the lung and bowel in UC rat models after the treatment of Sodium Houttuyfonate combined with Matrine. MethodUC rat models were established with the mucous membrane of colon allergize combined with TNBS-alcohol enteroclysis for 1 week and 5 weeks. 1-week experimental rats were divided into normal group and model group, 5/each group. 5-weeks experimental rats wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Recent research has demonstrated that there is a pathological connection between the lung and bowel with the longer course of the disease, the greater extent of the disease, and the more severe the pulmonary function damage is in individuals with UC (14). Animal experiments have also noted that rat models of UC exhibited lung pathological injury (14)(15)(16).…”
Section: Role Of Pulmonary Function Testing In Inflammatory Bowel Dis...mentioning
confidence: 99%
“…Recent research has demonstrated that there is a pathological connection between the lung and bowel with the longer course of the disease, the greater extent of the disease, and the more severe the pulmonary function damage is in individuals with UC (14). Animal experiments have also noted that rat models of UC exhibited lung pathological injury (14)(15)(16).…”
Section: Role Of Pulmonary Function Testing In Inflammatory Bowel Dis...mentioning
confidence: 99%